Supply Chain Analysis, Innovative Technology, Distribution, and Consumer Perception in Supporting the Sustainability of Hydroponic Vegetable Business - Rahmawati, Anisa (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research purposes: Analyzing the supply chain, Innovative technology, distribution and consumer perception. Design/Method/Approach: Study     Qualitative Descriptive forunderstanding Supply chain analysis, among others farmers, distributors, and consumers. Data analysis was carried out with data reduction on the results of the interviews conducted on selected informants. Research Findings:  The results of this study indicate that to support the sustainability of the hydroponic vegetable business, it is necessaryGood and correct process, Diverse distribution network, Customer satisfaction and consumer perception. Theoretical contribution / Originality:Adding theory about the importance of supply chains for sustainability hydroponic vegetable business. Practitioner/Policy Implications:The results of this study can adapted by similar hydroponic businesses. Research limitations: Time constraints that make the results that are get  less than optimal so that this research is not perfect.